Kewenangan Notaris dalam Mewujudkan Kebahagiaan - Sinaga, Roulinta Yesvery (PATTIMURA Legal Journal, 2023)
Introduction: Civil relations, especially engagement relations, are a major factor in the growth and development of society.The actual form of the resulting agreement is the choice of the parties, but for the purposes of evidentiary law, the form of the agreement in a notarial deed (written) has a stronger position. Purposes of the Research: The purpose of this study is to examine the authority of a notary in making authentic deeds and to review the existence of a notary's deed in providing happiness based on the agreement of the parties. Methods of the Research: This research was carried out in a normative juridical manner, using bibliographical data as secondary data to examine rules and norms in law. Results Originality of the Research: The authority of a notary in making agreements is a mandate. The freedom to contract the parties accompanied by the principle of good faith is then stated in a notarial deed that should give happiness to the contracting parties. The position of a notary as an intermediary must accommodate the needs of the parties, both from the pre-contract stage, and the contractual stage to the post-contract stage. The notarial deed is also a means of happiness and light for the contracting parties